2021
DOI: 10.1186/s12939-021-01395-5
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent, caregiver and community experiences with a gender transformative, social emotional learning intervention

Abstract: Background Inequitable gender norms, beliefs and behaviors, are shaped by learning experiences during key developmental stages in an individual’s life course, and can have negative impacts on health and well-being outcomes. Very early adolescence represents one stage when formative learning experiences about gender inequity can have the potential to support or hinder more equitable gender norms, beliefs and behaviors. The aim of this qualitative study was to evaluate the effect of a gender tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
10
0
2
Order By: Relevance
“…Interventions should also be gender transformative and include fathers and brothers who need to promote gender equity in families. [49,50] e assessment of different domains of gender disadvantage is a distinct strength of the study. In addition, we included in our study, girls who were out of school increasing the generalizability of the study as most studies among adolescent girls are done among those attending school or college.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions should also be gender transformative and include fathers and brothers who need to promote gender equity in families. [49,50] e assessment of different domains of gender disadvantage is a distinct strength of the study. In addition, we included in our study, girls who were out of school increasing the generalizability of the study as most studies among adolescent girls are done among those attending school or college.…”
Section: Discussionmentioning
confidence: 99%
“…This study is a three-arm comparative effectiveness trial evaluating Discover [ 17 , 42 ], an intervention designed to support learning social emotional mindsets and skills among very young adolescents (10-11 years old). Learning content included 6 modules targeting growth mindset, curiosity, generosity, persistence, purpose, and teamwork.…”
Section: Methodsmentioning
confidence: 99%
“…There is extensive literature that explores interventions targeting social emotional outcomes, including gender norms and beliefs among adolescents. Each of these studies focus on domains of social emotional learning and gender equity, such as sexual and reproductive health [ 16 ], role of parents and community [ 17 ], gender-based violence [ 18 ], and health and well-being [ 19 , 20 ]. The Global Early Adolescent Study (GEAS) conducted with 10–14-year-olds in the Democratic Republic of Congo, found that mixed gender group sessions were a valuable implementation strategy to maximize learning positive gender norms and beliefs [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study includes follow-up data from adolescents who participated in Discover Learning, a social emotional learning intervention delivered from July to August 2019. Articles detailing the study protocol of the 2019 Discover Learning intervention and results are available in peer review publications (19,42,43). While the social emotional learning intervention did not include Utu content, it is possible that improvements in social emotional skills and mindsets resulting from participation in Discover biased results for the non-orphan sample.…”
Section: Limitationsmentioning
confidence: 99%